Efforts to Improve Social Studies Learning Outcomes through a Make A Match Model Assisted by Word Wall in Class V UPT SDN 289 Pinrang - Hasnawiah Hasnawiah; Ilham Assidig; Rahmat Said (Universitas Muhammadiyah Enrekang, 2024)
This research aims to describe the implementation of the Make A Match model assisted by Word Wall, analyze the improvement of learning outcomes, and describe student responses in social studies learning in fifth grade at UPT SDN 289 Pinrang. The research employed Classroom Action Research method in two cycles through planning, action, observation, and reflection stages. Data collection techniques included observation, tests, questionnaires, and documentation. Data analysis techniques used descriptive quantitative and qualitative approaches. The results showed: First, the implementation of Make A Match model assisted by Word Wall was carried out through steps where the teacher explained material using Word Wall, introduced the model and game rules, divided students into two groups, students searched for matching cards, presented results, and the teacher facilitated confirmation discussions. Teacher activity increased from 78.57% in cycle I to 90.48% in cycle II, while student activity increased from 75% to 89.71%. Second, student learning outcomes improved from the initial condition with classical completeness of 35.71% and an average score of 65.71, to 64.29% with an average score of 76.07 in cycle I, and 85.71% with an average score of 83.21 in cycle II. Third, student responses to learning were very positive with an increase in percentage from 79% in cycle I to 86.5% in cycle II.